The Fungal-Specific Transcription Factor VpFSTF1 Is Required for Virulence in Valsa pyri - Kange, Alex Machio; Xia, Ai; Si, Jierui; Li, Bingxin; Zhang, Xiong; Ai, Gan; He, Feng; Dou, Daolong (Frontiers in Microbiology, 2020)
Valsa pyri is the causal agent of pear canker disease, which leads to enormous losses of pear production in eastern Asian, especially China. In this study, we identified a fungal-specific transcription factor 1 (termed as VpFSTF1) from V. pyri, which is highly conserved in fungi. To characterize its functions, we generated mutant and complementation strains in V. pyri and found that △VpFSTF1 mutants lost the ability to form fruiting bodies along with the reduced virulence. The radial growth of △VpFSTF1 mutant was sensitive to increasing concentrations of hydrogen peroxide (H2O2) and salicylic acid (SA). Moreover, RNA-sequencing (RNA-Seq) analysis of wild-type and △VpFSTF1 mutant strains was performed, and the results revealed 1,993 upregulated, and 2006 downregulated differentially expressed genes (DEGs) in the mutant. The DEGs were corresponding to the genes that are involved in amino acid metabolism, starch, and sucrose metabolism, gluconeogenesis, citrate cycle, and carbon metabolism. Interestingly, pathogen host interaction (PHI) analysis showed that 69 downregulated genes were related to virulence, suggesting that they might function downstream of VpFSTF1. Nine DEGs were further validated by quantitative reverse transcription-polymerase chain reaction (qRT-PCR), and the results were consistent with RNA-seq analysis. Furthermore, promoter regions were predicted, and VpFSTF1 binding activity was assessed. We demonstrated that five promoters are directly or indirectly targeted by VpFSTF1, including catalase-related peroxidase (VPIG_01209) and P450 family genes. Taken together, these findings indicate that VpFSTF1 is crucial for the virulence of V. pyri via direct or indirect regulation of downstream genes expression and lay an important foundation for understanding the molecular mechanism of V. pyri infection.